Information Acceptance of EWOM And Purchase Intention Through Haul Videos Youtube - Martawilaga, Ayu Indriani; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2016)
Abstract. Haul video is a new platform of EWOM that provides honest feedback towards fashion products that less persuassive and more attractive visual and information than heavy pages of fashion magazine. Based onÃ‚Â TuburalInsights.com on Ã¢â‚¬Å“YouTube Beauty IndustryÃ¢â‚¬Â, YouTube vloggers and haul video control 97% of conversations around beauty and brands on YouTube. They have 10x more videos on their channels than the brand itself. ThatÃ¢â‚¬â„¢s why female consumers are more engage with haul videos that made and spread by ordinary internet user that has passion in fashion. Haul videos can be very beneficial to fashion retailers. However, haul videos can be a source of problem if the haul video give a negative perception towards the brands or products so that it will decrease intention to purchase. Therefore, this study was conducted to enrich and improve the scarcity in previous studies about haul videos. By understanding the factors of haul videos, fashion retailers can use haul video as their new channel promotion effectively. The research excuted in Bandung and Jakarta. Questionnaire with Argument Quality, Source Credibility, Source Attractiveness, Perceived Usefulness, Source Style, Information Acceptance of EWOM, and Purchase Intention are filled by 350 women respondents in age range of 16-35 years old who are internet active user as the object of this research. The data collected was analyzed using Microsoft Excel, IBM SPSS Statistic 23 and processed through Frequency Analaysis, and Multi Linear Regression. The result found that most of haul video watchers come from age 16-20 years old and work as university student. The result found that before have purchase intention, the information acceptance of EWOM through haul videos is needed. The factors that influence the information acceptance of EWOM are Argument Quality, Source Credibility, Source Attractiveness, and Source Style. Factors that influence purchase intention directly are Source Attractiveness and Information Acceptance of EWOM. Based on the result, fashion retailer that wants to make haul videos as their channel promotion can do partnership with haul video makers that credible, have good argument quality, represent the target market of the products, and creative in delivering the haul video. Beside that, fashion retailer should control the content og haul video too.